2021
DOI: 10.7759/cureus.15804
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Embolization of Fisch Grades II–IVa Juvenile Nasopharyngeal Angiofibromas: Transarterial Embolization in the Age of Onyx

Abstract: The current mainstay treatment for juvenile nasopharyngeal angiofibromas (JNAs) is surgical resection, but embolization of primary feeding arteries through endovascular transarterial and direct tumoral puncture embolizations with various agents has been described. We describe a single institutional experience with JNA embolization utilizing Onyx (Medtronic, Dublin, Ireland). MethodsA retrospective records review was performed to identify patients who underwent embolization for devascularization of Fisch grades… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Although Onyx formulation 34 (more viscous) is more frequently used, in the literature also, formulation 18 (more fluid) has been employed [ 9 , 10 ] for hypervascular lesion treatment and both can be used in the same procedure [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although Onyx formulation 34 (more viscous) is more frequently used, in the literature also, formulation 18 (more fluid) has been employed [ 9 , 10 ] for hypervascular lesion treatment and both can be used in the same procedure [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cyanoacrylate and Onyx are both liquid polymers that result in permanent casting and thrombosis of vessels once the materials contact blood 32 . Both materials have been shown to be safe and effective in reducing intraoperative blood loss and improving visualization during JNA resection, although no study included in this analysis utilized Onyx 9,33‐35 . Reports of embolic stroke have been reported with these materials, highlighting the need for caution 36,37 .…”
Section: Discussionmentioning
confidence: 99%
“…32 Both materials have been shown to be safe and effective in reducing intraoperative blood loss and improving visualization during JNA resection, although no study included in this analysis utilized Onyx. 9,[33][34][35] Reports of embolic stroke have been reported with these materials, highlighting the need for caution. 36,37 While cyanoacrylate rapidly polymerizes, and is often diluted to prolong the polymerization time, Onyx polymerizes more slowly, affording a prolonged injection period.…”
Section: Embolic Materialsmentioning
confidence: 99%
“…Typically, angiography with embolization is performed 24–72 h prior to surgery. A variety of embolic agents are employed, frequently including polyvinyl alcohol, gelatin sponge, microcoils, and radiopaque liquid embolic agents (e.g., Onyx, ethylene vinyl alcohol copolymer) 5,777,795–799 . Numerous studies have shown that preoperative embolization is associated with reduction in intraoperative blood loss, though some studies suggest this benefit is limited to the advanced‐stage cases 5,777,796,797,800 .…”
Section: Benign Vascular Neoplasms and Lesionsmentioning
confidence: 99%